Gastrulation Screening to Identify Anti-metastasis Drugs in Zebrafish Embryos - Joji Nakayama; Hideki Makinoshima; Zhiyuan Gong (Bio-Protocol, 2022)
Few models exist that allow for rapid and effective screening of anti-metastasis drugs. Here, we present a drug screening protocol utilizing gastrulation of zebrafish embryos for identification of anti-metastasis drugs. Based on the evidence that metastasis proceeds through utilizing the molecular mechanisms of gastrulation, we hypothesized that chemicals interrupting zebrafish gastrulation might suppress the metastasis of cancer cells. Thus, we developed a phenotype-based chemical screen that uses epiboly, the first morphogenetic movement in gastrulation, as a marker. The screen only needs zebrafish embryos and enables hundreds of chemicals to be tested in five hours by observing the epiboly progression of chemical-treated embryos. In the screen, embryos at the two-cell stage are firstly corrected and then developed to the sphere stage. The embryos are treated with a test chemical and incubated in the presence of the chemical until vehicle-treated embryos develop to the 90% epiboly stage. Finally, positive ‘hit’ chemicals that interrupt epiboly progression are selected by comparing epiboly progression of the chemical-treated and vehicle-treated embryos under a stereoscopic microscope. A previous study subjected 1,280 FDA-approved drugs to the screen and identified adrenosterone and pizotifen as epiboly-interrupting drugs. These were validated to suppress metastasis of breast cancer cells in mice models of metastasis. Furthermore, 11β-hydroxysteroid dehydrogenase 1 (HSD11β1) and serotonin receptor 2C (HTR2C), the primary targets of adrenosterone and pizotifen, respectively, promoted metastasis through induction of epithelial-mesenchymal transition (EMT). Therefore, this screen could be converted into a chemical genetic screening platform for identification of metastasis-promoting genes.Graphical abstract: